Intervention against the stigmatization of men with eating disorders in primary care (iSMEsH): Protocol for a randomized mixed-methods evaluation trial - Martin S. Lehe; Georg Halbeisen; Georgios Paslakis (PLoS ONE, 2025)
Introduction Eating disorders (EDs) are a significant public health concern, yet men remain underrepresented in research and care, partly due to stigmatization. This stigmatization contributes to reduced help-seeking and recognition of ED symptoms in men. To address this, targeted interventions for healthcare professionals are needed. The iSMEsH intervention aims to sensitize general practitioners (GPs) in Germany to EDs in men, impart relevant knowledge and skills, and counter the perception of EDs as “women’s diseases”. Methods We will evaluate the iSMEsH intervention regarding its effects on biased attitudes, knowledge, and self-efficacy among GPs. A sequential explanatory mixed-methods design (QUAN → qual) will be applied in three steps: (1) pre-implementation focus groups and a panel discussion with individuals with lived ED experience and GPs to design the intervention, (2) conduction of a randomized, wait-list controlled trial of the online training trial with GPs and medical students, and (3) post-implementation qualitative interviews with GPs. Quantitative data (step 2) will be analyzed using mixed-measures ANOVAs and contrast analyses (per-protocol) as well as corresponding 2 × 3 linear mixed models with fixed and random effects (intention-to-treat). Qualitative data from step 3 will be analyzed using thematic analysis as outlined by Braun and Clarke (2006). Ethical approval was granted by the Ruhr-University Bochum Ethics Committee (AZ 2023−1106). Participants will provide written or digital informed consent. Discussion The intervention seeks to reduce stigma against men with EDs in primary care by improving GPs’ and medical students’ knowledge, attitudes, and self-efficacy. Strengths include the comprehensive mixed-methods approach and involvement of people with lived experience. Limitations are reliance on self-report and short-/intermediate-term outcomes. If effective, iSMEsH may offer a foundation for future stigma-reduction strategies in healthcare.